Study of the crystal structure and magnetic properties of the phase obtained from (C2H3O2)2Fe and (C2H3O2)2Sr obtained by the polyol method - Tenorio, F. N.; Sánchez-De Jesús, F.; Bolarin-Miró, A. M.; Menéndez, N.; Vera-Serna, P.; Palomino , R. L.; Barba-Pingarrón, A. (Tópicos de Investigación en Ciencias de la Tierra y Materiales, 2016)
We proposed that during the synthesis of Sr doped hematite, the Sr ion is introduced into the crystal structure of the magnetite and coexist two phases (hematite and magnetite). To confirm the previous statement, we synthetized two kind of powder, for a hand one pure phase of hematite and for the other hand the Sr doped hematite. In this study is presented the characterization of crystal structure and the magnetic properties of both samples. The X Ray Diffraction study of the sample without strontium shows only a Fe2O3 phase, but the sample with strontium shows two phases (hematite and magnetite). The magnetic characterization of the sample without strontium indicates that the material is a ferromagnetic material with low magnetization (1 emu/g), this behavior is typical of hematite. The hysteresis loops of sample with strontium confirm the coexistence of two phases. Any characterizations provide information of Sr ion but we can suppose that the strontium is into the crystal structure of magnetite. The Mössbauer spectroscopy of sample without strontium shows only a sextet of hematite.